A QTAIM and stress tensor perspective of large‐amplitude motions of the tetrasulfur tetranitride S4N4 molecular graph. Issue 13 (8th March 2016) - Xu, Yuning; Xu, Tianlv; Jiajun, Dong; Kirk, Steven R.; Jenkins, Samantha
Abstract : The nature of the bonding interactions including the intramolecular SS interactions in tetrasulfur tetranitride, S4 N4 are probed by performing very large amplitude vibrations of all of the 18 normal modes of vibration. The QTAIM and stress tensor point properties are ‐then investigated and found to be highly dependent on the mode of vibration. A considerable degree of metallicity ξ(r b ) is found for the SS and SN bonding interactions. A unique bonding feature is found for a small amplitude vibration of the most anharmonic mode of this investigation, mode 2, where the SS bond critical point (BCP) transforms from a closed‐shell SS BCP to a shared‐shell SS BCP. We find 17 new unique QTAIM topologies for the molecular graphs corresponding to the 18 modes of vibration along with seven "missing" topologies that are mapped onto a spanning 2‐D Quantum topology Phase Diagram (QTPD). In addition, eleven unique topologies existing on 3‐D QTPDs are found due to the presence of non‐nuclear attractors (NNAs). We use the stress tensor eigenvalues to explain the invariance of the numbers and types of QTAIM critical points. The applicability of both the stiffness S and stress tensor stiffness S σ are also explored. Two new bond measures are introduced, a polarizability P and the stress tensor polarizability P σ which are derived from the stiffness S and stress tensor stiffness S σ, respectively. © 2016 Wiley Periodicals, Inc. Abstract : Tetrasulfur tetranitride, S4 N4 can form a large number of compounds that have been experimentally obtained, including the long chain polymeric sulfur nitride and a variety of small molecules produced from the polymer. The structural flexibility of the molecule is one of the most important factors affecting the reactivity of S4 N4. The QTAIM and stress tensor point properties are found to be highly dependent on the mode of vibration of the molecules.